2010
DOI: 10.1002/dc.21520
|View full text |Cite
|
Sign up to set email alerts
|

Primary CNS plasmablastic lymphoma: Report of a case with CSF cytology, flow cytometry, radiology, histological correlation, and review of the literature

Abstract: Plasmablastic lymphoma (PBL) is a rare subtype of diffuse large B cell lymphoma and commonly presents as an oral mass in HIV patients. Extraoral PBL has been reported, including one case of primary central nervous system PBL (PCNSPBL). The cytological features of PBL have been described, including cerebrospinal fluid (CSF) cytology findings for secondary CNS involvement by PBL. The etiology of PCNSPBL is still unknown. We report here the CSF cytology of a PCNSPBL, which shows a hypercellular specimen composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Plasmablastic lymphoma (PBL) is an aggressive disease that is highly associated with human immunodeficiency virus (HIV) infection and other immunodeficiencies, but it is also described in immunocompetent individuals (46%) . PBL usually occurs in the oral cavity and jaw, and less commonly in extraoral sites, mainly the gastrointestinal tract, skin, and lymph nodes . It is characterised by plasmablastic features, an immunophenotypic profile close to that of plasma cells, Epstein–Barr virus (EBV) positivity, and MYC dysregulation …”
Section: Introductionmentioning
confidence: 99%
“…Plasmablastic lymphoma (PBL) is an aggressive disease that is highly associated with human immunodeficiency virus (HIV) infection and other immunodeficiencies, but it is also described in immunocompetent individuals (46%) . PBL usually occurs in the oral cavity and jaw, and less commonly in extraoral sites, mainly the gastrointestinal tract, skin, and lymph nodes . It is characterised by plasmablastic features, an immunophenotypic profile close to that of plasma cells, Epstein–Barr virus (EBV) positivity, and MYC dysregulation …”
Section: Introductionmentioning
confidence: 99%
“…In one series of 138 patients, all those who relapsed died from their lymphoma (Todeschini et al 2004 ), although another series from the MD Anderson Cancer Center had 42 % longterm survivors (Popat et al 1998 Rare cases have been reported in the brain parenchyma or ventricles (Kelley et al 2005 ) (Fig. Rare cases may demonstrate plasmablastic features (Urrego et al 2011 ). Their pathologic features are similar to non-CNS sites; however, their detailed histopathologic features are not well characterized.…”
Section: Treatment Of Recurrent Diseasementioning
confidence: 99%
“…So far there were two cases of primary central neurous system PBL reports in the world. One case occurred in the right basal ganglian [1], another occurred in the left anterior frontal lobe [2]and both patients were HIV-positive. Here we report a HIV-negative but EBV-positive patient with a primary CNS plasmablastic lymphoma, a rare variant of DLBCL.…”
Section: Introductionmentioning
confidence: 99%